The interplay of polygenic plasticity and adrenocortical activity as sources of variability in pathways among family adversity, youth emotional reactivity, and psychological problems. (May 2020) - Davies, Patrick T.; Cicchetti, Dante; Thompson, Morgan J.; Bascoe, Sonnette M.; Cummings, E. Mark
Abstract: This study examined the interplay between a polygenic composite and cortisol activity as moderators of the mediational pathway among family adversity, youth negative emotional reactivity to family conflict, and their psychological problems. The longitudinal design contained three annual measurement occasions with 279 adolescents (Mean age = 13.0 years) and their parents. Latent difference score analyses indicated that observational ratings of adversity in interparental and parent–child interactions at Wave 1 predicted increases in a multimethod, multi-informant assessment of youth negative emotional reactivity to family conflict from Waves 1 to 2. Changes in youth negative emotional reactivity, in turn, predicted increases in a multi-informant (i.e., parents, adolescent, and teacher) assessment of psychological problems from Waves 1 to 3. Consistent with differential susceptibility theory, the association between family adversity and negative emotional reactivity was stronger for adolescents who carried more sensitivity alleles in a polygenic composite consisting of 5-HTTLPR, DRD4 VNTR, and BDNF polymorphisms. Analyses of adolescent cortisol in the period surrounding a family disagreement task at Wave 1 revealed that overall cortisol output, rather than cortisol reactivity, served as an endophenotype of the polygenic composite. Overall cortisol output was specifically associated with polygenic plasticity and moderated the association between family adversity and youth negative emotional reactivity in the same for better or for worse manner as the genetic composite. Finally, moderator-mediated-moderation analyses indicated that the moderating role of the polygenic plasticity composite was mediated by the moderating role of adolescent cortisol output in the association between family adversity and their emotional reactivity.